Priming cells for their final destination: microenvironment controlled cell culture by a modular ECM-mimicking feeder film1. (11th September 2015) - Barthes, Julien; Vrana, Nihal E.; Özçelik, Hayriye; Gahoual, Rabah; François, Yannis N.; Bacharouche, Jalal; Francius, Grégory; Hemmerlé, Joseph; Metz-Boutigue, Marie-Hélène; Schaaf, Pierre; Lavalle, Philippe
<x xml:space="preserve">Abstract</x> A modular ECM-mimicking coating for cell culture is designed and acts as gel-feeder providing simultaneously ECM components, growth factors, stiffening elements and antimicrobials.